Hitra urbanizacija na Bjelašnici - Krivošić Dizdarević, Leila (Urbani izziv, 2024)
In the early 2000s, Mount Bjelašnica, one of the four Olympic mountains around the city of Sarajevo, experienced rapid urbanization. In an attempt to create a modern mountain resort, but without a general design vision and with substantial criticism from residents, new hotels and other accommodation were built. This article offers insight into the development of the mountain resort at Babin Do on Mount Bjelašnica, comparing it with the development of similar mountain resorts in France. Case studies are the mountain villages of Flaine and Les Arcs, both created in the 1960s by prominent architects as a part of the government program Plan Neige; however, they have largely been changed and extended since then. The findings show certain similarities in the urban planning and architecture at Babin Do with the case studies examined in France, even over a period of sixty years. Although certain buildings in Babin Do create a positive mountain resort ambience, the absence of a regulatory plan that has caused overcrowding with accommodation, and the lack of common public space along with poor all-year activities show that this mountain resort cannot be considered a successful development. Further damage to nature should be minimized, and development should have been more considered and sustainable.
Keywords: francoski program Plan Neige; gorska letovišča; mountain resorts; olimpijske igre; Olympic Games; Sarajevo; urbanizacija; urbanization